2010
DOI: 10.1007/s10517-010-0918-z
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and In Vitro Induced Apoptosis of Lymphocytes and Neutrophils in Patients with Alcohol Dependence

Abstract: Spontaneous and induced apoptosis of neutrophils and lymphocytes was studied in alcoholics during the abstinent syndrome and in healthy individuals. In alcoholics, the levels of lymphocyte and neutrophil apoptosis at the receptor and cellular levels were higher than in healthy subjects. Blood cells from alcohol addicts and normal individuals similarly react to stimuli (hyperthermia and synthetic glucocorticoid prednisolone) in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
1
0
1
Order By: Relevance
“…It has been reported that in alcoholic patients oxidative stress contributes strongly to forming somatic complications [ 64 ], disturbance of immune status [ 65 ], and induction of apoptosis [ 66 ]. In alcoholism, formation of OS can be increased by ethanol, the concentration of which significantly exceeds the norm in patients, as well as the toxic metabolite of ethanol-acetaldehyde, whose level also increases in the organism during alcoholic intoxication.…”
Section: Correction Of Oxidative Stress With Carnosine In Alcoholimentioning
confidence: 99%
“…It has been reported that in alcoholic patients oxidative stress contributes strongly to forming somatic complications [ 64 ], disturbance of immune status [ 65 ], and induction of apoptosis [ 66 ]. In alcoholism, formation of OS can be increased by ethanol, the concentration of which significantly exceeds the norm in patients, as well as the toxic metabolite of ethanol-acetaldehyde, whose level also increases in the organism during alcoholic intoxication.…”
Section: Correction Of Oxidative Stress With Carnosine In Alcoholimentioning
confidence: 99%
“…Полученные данные о нарушениях процессов запрограммированной клеточной гибели, в частности об изменениях уровня внутриклеточных регуляторных белков в условиях окислительного стресса и под воздействием этанола согласуются с литературными данными[11]. Tejedo J. C. с соавторами[12] показали токсическое воздействие оксида азота на клетки RINm5F, в результате которого происходит индукция апоптотических событий, таких как выделение цитохрома С из митохондрий, регуляция внутриклеточного белка Bcl-2, активация каспазы 3, фрагментация ДНК.…”
unclassified